Ireland : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the results of the assessment of public investment management in Ireland. To support Ireland's economic and social development to 2040, the government is preparing a new spatial planning strategy, dubbed the National Planning Framework. This framework, and an associated 10-year capital plan-both of which will be released at the end of 2017-will support the government's efforts to redirect infrastructure investment to areas that cut across traditional departmental and sectoral boundaries. This new strategy strongly emphasizes the development of urban areas outside Dublin, including four new Metropolitan Areas. Ensuring that the various national, sectoral, regional, and local plans are aligned, integrated, and realistic is essential to delivering on these lofty expectations.